Causes of the drastic change in sea ice on the southern northwind ridge in July 2019 and July 2020: From a perspective from atmospheric forcing - Xinyuan, Lv; Na, Liu; Lina, Lin; Lei, Yang; Yunbo, Li; Long, Fan; Hongxia, Chen; Yingjie, Wang; Bin, Kong; Yuyuan, Zhang; Ning, Liu (Frontiers in Earth Science, 2022)
Arctic sea ice is a key factor in high–latitude air–sea–ocean interactions. In recent decades, its extent has been decreasing in all seasons with large interannual variability, especially for the Northwind Ridge. After removing the trend in the changes during July 1979 to 2020, 2019 had an abnormally low value, while the following year, 2020, had an abnormally high value. The underlying processes driving this variability in July near the southern Northwind Ridge, which is one of the areas with the most drastic changes in Arctic, are not well understood. There, we demonstrated that the shortwave radiation anomaly in July is the direct reason for the sea ice anomaly in July 2019 and July 2020. Importantly, the total energy surplus in the spring of 2019 (enough to melt ∼18 cm of sea ice) and 2020 (potentially melting ∼11 cm of sea ice) indirectly influenced the sea ice. The abnormal change in moisture and its convergence mainly caused by atmospheric circulation were the main reasons for the longwave radiation and latent flux anomalies. Cloud water mainly affected shortwave radiation, including the positive net shortwave radiation anomaly in May 2019.